The Construction of an Interregional Input–Output Table for Sabah, Sarawak and Peninsular Malaysia: An Application to Government Expenditure - Chun Sian, Pang; Mohd Khairul Hisyam, Hassan (Human Resource Management Academic Research Society (HRMARS), 2026)
This study develops the 2015 Interregional Input–Output (IRIO) Table for Sabah, Sarawak, and Peninsular Malaysia to examine the structural characteristics and the impacts of government expenditure on output, income, and employment. The IRIO framework was developed using the non-survey RAS method, supported by national IO accounts and adjusted for regional differences. While data challenges included incomplete regional statistics, unpublished figures, and the need for aggregation from 120 to 30 sectors, the resulting framework provides a consistent and policy-relevant picture of Malaysia’s interregional economy. Results reveal the dominant role of Peninsular Malaysia in driving national output, while highlighting untapped growth potential in Sabah and Sarawak. Heterogeneous expenditure impacts reflect structural differences, with Peninsular Malaysia’s strong forward linkages contrasting with weaker linkages in East Malaysia. These findings contribute to both methodological innovation and policy debates by demonstrating how non-survey techniques can be applied in data-constrained contexts, while also offering actionable insights for fiscal policy, regional development, and interregional integration.